PENINGKATAN KETERAMPILAN BERBICARA DALAM MENANGGAPI PEMBACAAN CERPEN MELALUI MODEL PEMBELAJARAN KEPALA BERNOMOR STRUKTUR PADA PESERTA DIDIK DI MTsN 4 JOMBANG - SHOLIHAH, IMRO’ATUS (Inovasi: Jurnal Diklat Keagamaan, 2020)
Student learning outcomes are strongly influenced by the quality of learning carried out in madrasah. Onething that determines the quality of learning is the use of learning methods and models that are appropriateor in accordance with the material being taught. The results of learning speaking skills material in responseto short story reading at MTsN 4 Jombang are still very low. For this reason, the researcher wants to makechanges so that learning outcomes can be increased, namely by applying the structure numbered headlearning model. This research is a Classroom Action Research which is carried out in 2 cycles with each cycleincluding planning, implementing actions, observing activities, and reflecting. The subjects of this studywere students of class IX A MTsN 4 Jombang even semester 2018/2019 with a total of 34 students. Thedata analysis used in this research is descriptive qualitative analysis. Data collection techniques were carriedout through student activity observation sheets, achievement tests for students’ learning competencies,interviews, and questionnaires. The results of this study are [1] the group discussion method with thenumbered head model can actively involve all students in discussion activities, is effective enough to fosterdiscipline, interest, cooperation, activeness, and responsibility of students and is proven to be effective inovercoming students’ difficulties. in expressing opinions and giving responses in short story reading; [2]the group discussion method with the numbered head model can improve Indonesian learning outcomes inspeaking skills, especially in response to short story reading. This is evidenced by the increase in Indonesianlearning achievement, the material ability to respond to short story reading from the initial conditions withan average value of 70 with 20 % completeness to the final condition in the second cycle, an average valueof 85 with a completeness of 85.70 % in class IX A MTsN students. 4 Jombang Even semester of the 2018/2019 academic year.